INTERCULTURAL GAMES OF MANAUS: ANALYSIS OF ROUNDS OF ARCHERY AND BLOWGUN. (Fiep Bulletin - online, 2012)
The present paper discusses the importance of the indigenous traditional sporting modalities – blowgun and archery disputed during the accomplishment of the First Indigenous Intercultural Games in the community of the Livramento in Manaus – AM, in the period of April 30 to May 01, 2011 opportunity in that were disputed indigenous traditional modalities and non indigenous modalities as volleyball, athletics, soccer. The used methodology was of the qualitative type through techniques as direct observation, analyze of content and non-directive interview. We noticed that in spite of the inclusion of non indigenous modalities and have been conducted in urban area, the traditional modalities were not forgotten. Instead, it was verified that have gained excellent participation and were very encouraged by the indigenous thus affirming the purpose of the Indigenous intercultural games: the invigoration, incentive and the appreciation of the traditional games.
Keywords: traditional games; games intercultural; Indigenous sport